2022
DOI: 10.1097/prs.0000000000010007
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Isolated Microtia: A Systematic Review and Meta-Analysis

Abstract: Background: Isolated microtia is a congenital facial anomaly, and its cause is unclear. This study systematically investigated related suspicious factors. Methods: A systematic review was conducted following the Preferred Reporting Items for Systematic Review and Meta-Analyses guidelines. Four databases were searched for eligible case-control and cohort studies. Odds ratios and 95% confidence intervals were calculated for each exposure variable if data from at least two eligible studies were provided. If not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Microtia is usually a congenital disorder that affects the hearing and psychological health of affected children. Many of the disease-candidate genes are involved in the proliferation and differentiation of auricle chondrocytes and, therefore, the development or growth of auricle cartilage ( Gendron et al, 2016 ; Huang et al, 2023 ). Here, we show that in young or adult mice, ablation of Bmpr1a in auricle chondrocytes, which are genetically labeled by Prrx1 , leads to rapid development of microtia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microtia is usually a congenital disorder that affects the hearing and psychological health of affected children. Many of the disease-candidate genes are involved in the proliferation and differentiation of auricle chondrocytes and, therefore, the development or growth of auricle cartilage ( Gendron et al, 2016 ; Huang et al, 2023 ). Here, we show that in young or adult mice, ablation of Bmpr1a in auricle chondrocytes, which are genetically labeled by Prrx1 , leads to rapid development of microtia.…”
Section: Discussionmentioning
confidence: 99%
“…Microtia causes hearing problems and delays in language learning ( Gendron et al, 2016 ). Genetic studies have shown that microtia is linked to mutations in ROBO1/ROBO2 , HOXA2 , SIX1/SIX5 , TBX1 , or CHUK in humans ( Cox et al, 2014 ; Huang et al, 2023 ; Lu et al, 2020 ; Quiat et al, 2022 ). In mice, Prrx1 and Prrx2, FGF, BMP, and Wnt have been shown to affect auricle development ( ten Berge et al, 1998 ; Xie et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Microtia is usually a congenital disorder that affects the hearing and psychological health of affected children. Many of the disease candidate genes are involved in the proliferation and differentiation of auricle chondrocytes and therefore the development or growth of auricle cartilage (Gendron et al, 2016; Huang et al, 2023). Here, we show that in young or adult mice, ablation of Bmpr1a in auricle chondrocytes, which are genetically labelled by Prrx1 , leads to rapid development of microtia.…”
Section: Discussionmentioning
confidence: 99%
“…Microtia causes hearing problems and delays in language learning (Gendron et al, 2016). Genetic studies have shown that microtia is linked to mutations in ROBO1/ROBO2 , HOXA2 , SIX , TBX1 , or CHUK in humans (Cox et al, 2014; Huang et al, 2023; Lu et al, 2020; Quiat et al, 2022). In mice, Prrx1 and Prrx2, FGF, BMP, and Wnt have been shown to affect auricle development (ten Berge et al, 1998; Xie et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Inherited defects, external factors, or the interaction between genes and external factors are the main causes of microtia. Epidemiological studies have found that environmental factors, including cold-like syndromes during pregnancy, a history of spontaneous abortion, vaginitis, cervicitis, and other infections, as well as exposure to toxic chemicals, such as polycyclic aromatic hydrocarbons, paints, and pesticides, are risk factors for the disease 6 . Evidence that strongly suggests a genetic cause for microtia includes the higher frequency of cases in monozygotic twins (38.5%) compared with dizygotic twins (4.5%); reporting of familial cases with autosomal recessive or dominant inheritance patterns linked to variable expression and incomplete penetrance; family history of disease in about 3% to 34% of cases; reporting of >18 different microtia-related syndromes, which include those associated with monogenic defects or chromosomal aberrations; and mouse models proving the genetic cause microtia 4 .…”
mentioning
confidence: 99%